Determinant Factors of Company Share Prices in Financial Sector Companies on The IDX - Donny Dharmawan; M. Anwar Karnadi; Ratnawita Ratnawita; Suratman Suratman; Loso Judijanto (Yayasan Riset dan Pengembangan Intelektual, 2023)
Share prices are greatly influenced by supply and demand for shares, the more people who buy shares, the higher the price. On the other hand, share prices can fall if many owners sell their shares. The aim of this study is to evaluate and analyze variables that can influence the share prices listed on the Indonesia Stock Exchange for the 2017-2019 period. These factors include EPS, ROE and DER. In this study, quantitative methods were applied with regression analysis. The research sample consists of 7 companies in the regular financial industry that provide quarterly financial statements from 2017 to 2021. After using the purposive sampling method, Eviews 10 was applied to analyze the data. Classical assumption testing, model feasibility analysis, panel regression analysis, and determination coefficient tests are processes that researchers use to test data. According to the results of the study, stock prices are strongly influenced by EPS and ROA, but stock prices are not influenced by DER. Financial sector companies that have below-average EPS ratio and negative values should realize that increased profits aim to improve investor welfare through dividends and/or capital gains.